2022
DOI: 10.3389/fpsyg.2022.848154
|View full text |Cite
|
Sign up to set email alerts
|

How Does Emotion Influence Time Perception? A Review of Evidence Linking Emotional Motivation and Time Processing

Abstract: Emotions have a strong influence on how we experience time passing. The body of research investigating the role of emotion on time perception has steadily increased in the past twenty years. Several affective mechanisms have been proposed to influence the passing of time. The current review focuses on how three dimensions of affect—valence, arousal, and motivation—are related to time perception. The valence-based model of time perception predicts that all positive affects hasten the perception of time and all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
1
14
1
Order By: Relevance
“…On the one hand, this result could be explained through the PA model, which suggests that high intensity of withdrawal-motivation emotion could allocate more attention resources compared with low intensity, resulting in more attention resources invested in the timing process and leading to an underestimation of duration (Gibbon et al, 1984; Lake et al, 2016). On the other hand, this study supplemented the findings of Gable and Poole (2012) and Gable et al (2016) and further confirmed the mechanistic role of motivation in time perception (Gable et al, 2022; Yin, Zhang, Liu, & Li, 2023). Specifically, approach motivation hastened the perception of time, while withdrawal motivation slowed it.…”
Section: Discussionsupporting
confidence: 85%
“…On the one hand, this result could be explained through the PA model, which suggests that high intensity of withdrawal-motivation emotion could allocate more attention resources compared with low intensity, resulting in more attention resources invested in the timing process and leading to an underestimation of duration (Gibbon et al, 1984; Lake et al, 2016). On the other hand, this study supplemented the findings of Gable and Poole (2012) and Gable et al (2016) and further confirmed the mechanistic role of motivation in time perception (Gable et al, 2022; Yin, Zhang, Liu, & Li, 2023). Specifically, approach motivation hastened the perception of time, while withdrawal motivation slowed it.…”
Section: Discussionsupporting
confidence: 85%
“…As with the factor of task difficulty, in this factor we studied how the participants' level of motivation affected their perception of time during online customization. It has been observed in previous psychological experiments that people with a goal-motivated mindset underestimate their perceptions of time (Gable et al, 2022). Thus, we hypothesize that customers with high motivation to customize the product underestimate the passage of time (H3); in other words, the p-rate is negatively correlated with customers' motivation for customization.…”
Section: Factors Affecting the Perception Of Timementioning
confidence: 83%
“…As with the factor of task difficulty, in this factor we studied how the participants' level of motivation affected their perception of time during online customization. It has been observed in previous psychological experiments that people with a goal-motivated mindset underestimate their perceptions of time (Gable et al. , 2022).…”
Section: Factors Affecting the Perception Of Timementioning
confidence: 94%
See 2 more Smart Citations